Un village planétaire, dit-on ? - Gilbert Elbaz (Études Caribéennes)
The present article introduces the articles of the issue of the journal Etudes Caribéennes, the theme of which is globalization. The introductory article reviews the theoretical literature on the concept of globalization, particularly the perspectives of the hyper-globalists, the skeptics, and the transformationalists. Analysis of the various articles leads the author to conclude that the majority of them side with transformationalism.